Ferroelectric materials for energy harvesting and storage - Maurya, Deepam; Pramanick, Abhijit; Viehland, Dwight Douglas, 1962- (Woodhead Publishing series in electronic and optical materials., 2021)
The need to more efficiently harvest energy for electronics has spurred investigation into materials that can harvest energy from locally abundant sources. Ferroelectric Materials for Energy Harvesting and Storage is the first book to bring together fundamental mechanisms for harvesting various abundant energy sources using ferroelectric and piezoelectric materials. The authors discuss strategies of designing materials for efficiently harvesting energy sources like solar, wind, wave, temperature fluctuations, mechanical vibrations, biomechanical motion, and stray magnetic fields. In addition, concepts of the high density energy storage using ferroelectric materials is explored. Ferroelectric Materials for Energy Harvesting and Storage is appropriate for those working in materials science and engineering, physics, chemistry and electrical engineering disciplines.